Parietin Cyclodextrin-Inclusion Complex as an Effective Formulation for Bacterial Photoinactivation - Abdallah Mohamed Ayoub; Bernd Gutberlet; Eduard Preis; Ahmed Mohamed Abdelsalam; Alice Abu Dayyih; Ayat Abdelkader; Amir Balash; Jens Schäfer; Udo Bakowsky (MDPI AG, 2022)
Multidrug resistance in pathogenic bacteria has become a significant public health concern. As an alternative therapeutic option, antimicrobial photodynamic therapy (aPDT) can successfully eradicate antibiotic-resistant bacteria with a lower probability of developing resistance or systemic toxicity commonly associated with the standard antibiotic treatment. Parietin (PTN), also termed physcion, a natural anthraquinone, is a promising photosensitizer somewhat underrepresented in aPDT because of its poor water solubility and potential to aggregate in the biological environment. This study investigated whether the complexation of PTN with (2-hydroxypropyl)-β-cyclodextrin (HP-β-CD) could increase its solubility, enhance its photophysical properties, and improve its phototoxicity against bacteria. At first, the solubilization behavior and complexation constant of the PTN/HP-β-CD inclusion complexes were evaluated by the phase solubility method. Then, the formation and physicochemical properties of PTN/HP-β-CD complexes were analyzed and confirmed in various ways. At the same time, the photodynamic activity was assessed by the uric acid method. The blue light-mediated photodegradation of PTN in its free and complexed forms were compared. Complexation of PTN increased the aqueous solubility 28-fold and the photostability compared to free PTN. PTN/HP-β-CD complexes reduce the bacterial viability of Staphylococcus saprophyticus and Escherichia coli by > 4.8 log and > 1.0 log after irradiation, respectively. Overall, the low solubility, aggregation potential, and photoinstability of PTN were overcome by its complexation in HP-β-CD, potentially opening up new opportunities for treating infections caused by multidrug-resistant bacteria.